2013
DOI: 10.1093/cercor/bht190
|View full text |Cite
|
Sign up to set email alerts
|

Training the Motor Cortex by Observing the Actions of Others During Immobilization

Abstract: Limb immobilization and nonuse are well-known causes of corticomotor depression. While physical training can drive the recovery from nonuse-dependent corticomotor effects, it remains unclear if it is possible to gain access to motor cortex in alternative ways, such as through motor imagery (MI) or action observation (AO). Transcranial magnetic stimulation was used to study the excitability of the hand left motor cortex in normal subjects immediately before and after 10 h of right arm immobilization. During imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
3
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 89 publications
(67 citation statements)
references
References 78 publications
(101 reference statements)
0
57
3
2
Order By: Relevance
“…Although previous studies demonstrated that immobilization affects motor performance (Bassolino et al, 2012) and cortical excitability (Avanzino et al, 2011;Bassolino et al, 2013;Huber et al, 2006), this works is, at the best of our knowledge, the first report demonstrating the plastic properties of PPS representation after non-use. Before immobilization, the farthest distance at which sounds speed up tactile RTs was between D1 and D2 (corresponding approximately to a sound position perceived between 85 and 7 cm from the arm), and after non-use, this distance shifted to a position between D2 and D3 (corresponding approximately to a location between 70 and 50 cm), suggesting that PPS boundary around the constrained arm contracted.…”
Section: Non-use But Not Overuse Affects Pps Representationmentioning
confidence: 59%
“…Although previous studies demonstrated that immobilization affects motor performance (Bassolino et al, 2012) and cortical excitability (Avanzino et al, 2011;Bassolino et al, 2013;Huber et al, 2006), this works is, at the best of our knowledge, the first report demonstrating the plastic properties of PPS representation after non-use. Before immobilization, the farthest distance at which sounds speed up tactile RTs was between D1 and D2 (corresponding approximately to a sound position perceived between 85 and 7 cm from the arm), and after non-use, this distance shifted to a position between D2 and D3 (corresponding approximately to a location between 70 and 50 cm), suggesting that PPS boundary around the constrained arm contracted.…”
Section: Non-use But Not Overuse Affects Pps Representationmentioning
confidence: 59%
“…Further, a recent work on transcranial magnetic stimulation by our group has demonstrated that the reduction of the excitability of the hand area typically recorded after immobilization can be fully compensated when individuals observed hand actions performed by others. This result suggests that action observation can prevent the cortical effects induced by inactivity in healthy adults …”
Section: Motor Facilitation Induced By Action Observation In Adults Amentioning
confidence: 73%
“…If alterations are established, interventions using motor imagery or action observation might be tested with the aim of maintaining motor representations and compensating for the lack of sensorimotor input during the period of injury [5,52].…”
Section: Introductionmentioning
confidence: 99%